2018
DOI: 10.1111/1756-185x.13312
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of antinuclear antibodies in hidradenitis suppurativa

Abstract: The prevalence of baseline ANA positivity in this HS population was similar to that seen in the general population (5.4%). The rate of seroconversion and drug-induced complications in this population were low.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Although autoantibodies have been previously identified in HS, for example anti-nuclear antibodies and anti-cyclic citrullinated peptide (Byrd et al, 2019, Carmona-Rivera et al, 2022, Mulani et al, 2018, they have all been associated more markedly with other autoimmune diseases (i.e. SLE and RA, respectively).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although autoantibodies have been previously identified in HS, for example anti-nuclear antibodies and anti-cyclic citrullinated peptide (Byrd et al, 2019, Carmona-Rivera et al, 2022, Mulani et al, 2018, they have all been associated more markedly with other autoimmune diseases (i.e. SLE and RA, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…These may include organ-specific self-proteins, for example thyroid peroxidase in Hashimoto's disease, but also chemically-modified antigens, such as deamidated peptides in coeliac disease and citrullinated peptides in rheumatoid arthritis. Elevated titers of antibodies against nuclear antigens and citrullinated peptides have also been observed in HS (Byrd et al, 2019, Mulani et al, 2018. However, to date, no diseasespecific autoantigens have been identified in HS.…”
Section: Introductionmentioning
confidence: 99%
“…A previous report about suppurative hidradenitis indicated that only 1 in 31 anti-TNF treated patients had a seroconversion after 0.9 years of treatment. 44 A proportional relationship between the time of the treatment and the seroconversion rate could be explained by the differences in seroconversion rates. 45 Only 3 out of 11 patients with previous negative ANA suffered a seroconversion in the ustekinumab group and no patient had a seroconversion in the vedolizumab group.…”
Section: Discussionmentioning
confidence: 99%